Sebuah Adobe Flash CS6 dalam Menghitung Luas dan Keliling Bangun Datar Pada Anak Diskalkulia - Sella Malinda; Mega Iswari; Jon Efendi (Jurnal Pendidikan Kebutuhan Khusus, 2020)
This research is based on the problems that appear in the field, that is children with dyscalculia in grade V SDN 08 Surau Gadang Padang who have problems in mathematics about calculate area and perimeter of plane figures. This research used quasi experimental design with one group pretest-posttest design type. The result of this study were obtained based on data analysis seen from pretest and posttest score. The data were processed using mann whitney test. For n1 = 5 and n2 = 5 at 95% significant level and α = 0,05 obtained Uhit = 0 and Utab = 4. The null hyphotesis is accepted because Uhit ≤ Utab. The use media-based learning adobe flash CS6 is not effective in improve ability to calculate area and perimeter of plane figures for children with dyscalculia in grade V SDN 08 Surau Gadang Padang.